2016
DOI: 10.3349/ymj.2016.57.6.1535
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Translabyrinthine Tumor Removal and Cochlear Implantation in Vestibular Schwannoma Patients

Abstract: Refinement of surgical techniques has allowed hearing preservation after tumor resection to be prioritized. Moreover, restoration of hearing after tumor removal can be attempted in patients with bilateral vestibular schwannomas or those with a schwannoma in the only-hearing ear. Cochlear implantation (CI) has emerged as a proper method of acoustic rehabilitation, provided that the cochlear nerve remains intact. Studies of electrical promontory stimulation in patients after vestibular schwannoma resection have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…13,14 There were 5 of the 21 subjects who either did not have open-set recognition tested or were not reported. [18][19][20][21] One of these subjects had subjective recognition, but formal testing was deferred due to the patient only speaking Spanish. 19 A subject detailed by dos Santos Neto et al showed improvement in both Ling Sound Test and identification of vocabulary extension compared to baseline measures.…”
Section: Speech Perception Outcomesmentioning
confidence: 99%
“…13,14 There were 5 of the 21 subjects who either did not have open-set recognition tested or were not reported. [18][19][20][21] One of these subjects had subjective recognition, but formal testing was deferred due to the patient only speaking Spanish. 19 A subject detailed by dos Santos Neto et al showed improvement in both Ling Sound Test and identification of vocabulary extension compared to baseline measures.…”
Section: Speech Perception Outcomesmentioning
confidence: 99%
“…13 Previous studies show a positive outcome in patients with sporadic VS in the only or better hearing ear, with similar prognosis to that in patients without VS who were treated with CI. 1,6,12,13,27 Cochlear implants after radiosurgery in patients with neurofibromatosis type 2-associated VS have been described, with significant restoration of hearing. 10 However, the lack of knowledge about the benefits of CI in patients with normal contralateral hearing still exists.…”
Section: The Role Of CImentioning
confidence: 99%
“…CI performance in our series (n = 19) did not differ from those reported previously (n = 39) as high, moderate, or poor CI benefit observed in 47%, 21%, and 32% of cases in our study and in 46%, 21%, and 33% of cases in those studies reported previously. Altogether considering our series with previous reports, 57 CIs and five ABIs were implanted to rehabilitate hearing in 58 sporadic VSs in the only hearing ear during the last 28‐year period (Table ) . Most of the patients have been operated on mainly by TL, apart from nine patients whose hearing was restored by CI without VS surgery (present study) .…”
Section: Discussionmentioning
confidence: 77%
“…Performance of CI for hearing rehabilitation in the literature (n = 38) and the present study. Data were not available in three cases published in two articles (Talbot et al and Kim et al ).…”
Section: Discussionmentioning
confidence: 99%